Chemokines in ICU Delirium: An Exploratory Study. (5th July 2022) - Smith, Ryan J.; Rabinstein, Alejandro A.; Cartin-Ceba, Rodrigo; Singh, Vijay P.; Lachner, Christian; Khatua, Biswajit; Trivedi, Shubham; Gajic, Ognjen
Abstract : OBJECTIVES: The pathophysiology of delirium is complex and incompletely understood. Inflammation is hypothesized to be integral to its development due to effects on blood brain barrier integrity, facilitation of leukocyte extravasation into brain parenchyma, and propagation of neuroinflammation. Septic shock is the prototypical condition associated with ICU delirium; however, the relative contribution of resultant hypotension and systemic inflammation to the development of delirium is unknown. DESIGN: This was a prospective exploratory study. SETTING: A multidisciplinary ICU at an academic medical center in Phoenix, AZ. PATIENTS: Critically ill patients older than or equal to 18 years old admitted to the ICU. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Screening for delirium was performed using the Confusion Assessment Method for the ICU tool. The levels of C-C motif ligand 2 (CCL2), C-C motif ligand 3, C-X-C motif chemokine ligand 1, C-X-C motif chemokine ligand 10, and interleukin-8 were measured in serum samples obtained within 12 hours of ICU admission. Univariate and multivariate analyses were performed to assess the association of delirium with patient data pertaining to hospital course, laboratory values, vital signs, medication administration, and levels of the aforementioned chemokines. Forty-one of 119 patients (34.5%) in the study cohort developed ICU delirium. Each chemokine studied was associated with delirium on univariate analyses; however, CCL2 was the only chemokine found to be independently associated with the development of delirium on multivariable analysis. The association of increased CCL2 levels with delirium remained robust in various models controlling for age, presence of shock, Sequential Organ Failure Assessment score, Acute Physiology and Chronic Health Evaluation IV score, mean arterial pressure at presentation, lowest mean arterial pressure, and total opioid, midazolam, propofol, and dexmedetomidine exposure. CONCLUSIONS: The demonstrated relationship between CCL2 and delirium suggests this chemokine may play a role in the development of delirium and warrants further investigation.